Efektivitas Home Visit dalam Program Penguatan Keluarga Oleh Sos Children’s Village Medan - Ruth Indah Triani Aruan; Randa Putra Kasea Sinaga (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2022)
Family strengthening program by SOS Children's Village Medan is one form of family level social intervention that aims to prevent conditions that resulting children being separated from their family, mainly from economic factors. In implementing, educators obliged to do home visits.  Home visit means that educator carried out in the client's home. One of the village assisted by this program is the village of kwala bekala, where most of the clients work in the informal sector and spend their daily lives working outside their home, thus hinder the process of home visits. In fact, through home visits, educators will be able to explore problems and developments experienced by clients that will affect the termination process.The purpose of this study is to know the effectiveness of home visits in Family strengthening programs by SOS Children’s  village. Techniques being used for data collection includes literature study, observation, interviews, and documentation. The data obtained in the field were analyzed qualitatively to obtain conclusions. The result of this study shows that home visits in this program have been effective, as measured by three approaches, namely, resource approach, the second approach is the process approach and lastly based on the target approach seen from the achievement of the home visit goal in this program.